Pelatihan Perpajakan UMKM di SMKN 2 Semarang - Prabasari, Bonita; Rohmawati, Lilik; Dewi Endah Amaliyah, Erlina (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The lack of student skills, especially in the practice of tax reporting and socialization of tax reporting for students, makes training necessary for students, where this understanding will be embedded in the minds of students when they can become taxpayers. Therefore, the community service team at the Semarang University proposed training activities on MSME taxation for students at SMKN 2 Semarang. The purpose of holding this activity is to provide tax reporting practices in accordance with applicable regulations and increase self-awareness to comply with paying taxes. Community service activities in the form of MSME taxation training are packaged in seminars containing hands-on practice, namely the practice of simple income tax calculations, as well as the final tax reporting mechanism (Final Income Tax) using the DJP System in accordance with the latest tax laws. Tax training was held in October 2022 in the SMKN 2 Semarang. After the activity is carried out, the results of the pretest and posttest can be concluded that students can understand the steps for reporting MSME business taxation properly and correctly according to applicable regulations. Therefore, tax training especially for MSMEs must be carried put early on to raise awareness of tax reporting for graduates, especially those who are going to be entrepreneurs and work so that they can carry out MSME business tax reporting practices properly and correctly according to applicable regulations